Going on the long race? Employment duration and (de)regulation of experimental stochastic labor markets - Siegfried K. Berninghaus; Sabrina Bleich; Werner Güth (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
If the future market wage is uncertain, engaging in long-term employment is risky, with the risk depending on how regulated the labor market is. In our experiment long-term employment can result either from offering long-term contracts or from repeatedly and mutually opting for rematching. Treatments differ in how regulations restrict the employer's flexibility in adapting the employment contract to changes of the market (wage). All treatments allow for longer contract duration as well as for mutually opting to be rematched. Effort is chosen by employees after a contract is concluded. Treatments vary from no flexibility to no restriction at all. Will more (downward) flexibility be used in ongoing employment but reduce efficiency? If so, deregulation may weaken rather than promote labor market efficiency. And will regulation crowd out long-term employment, either in the form of long-term contracts or voluntary rematching?
Keywords: C72; C90; F16; J21; J24; L10; 330; deregulation; employment contracts; wage flexibility; principal-agent theory; experimental economics; repeated interaction; Arbeitsvertrag; Wiederholte Spiele; Arbeitsmarktflexibilisierung; Lohnrigidität; Agency Theory; Test